Applying culturomics to understand the motives behind the surrender of pet gibbons: Evidence from Indonesia - AFRIZAL MAULANA ABDI (Society for Indonesian Biodiversity, 2023)
Abstract. Abdi AM. 2023. Applying culturomics to understand the motives behind the surrender of pet gibbons: Evidence from Indonesia. Biodiversitas 24: 4606-4616. Seven of nine gibbon (Hylobatidae) species in Indonesia are protected by national regulation with threats to habitat fragmentation and illegal trade. People persist in owning gibbons as pet animals, violating the protected species law. To date, numerous pet gibbons have been surrendered to the authorities, which could result from intensified public awareness. More targeted demand reduction campaigns may be possible with a better understanding of the motivations behind these handovers. This study aims to document gibbon surrenders by the public to authorities and the motives behind these actions. Instagram posts and online local news were collated and analyzed between 2016 and 2023, comprising information on gibbon handovers to the authorities. From the 138 posts analyzed, 161 gibbon individuals, including 6 species from Sumatra (47.2%), Kalimantan (29.8%), Java (21.7%), and Bali (1.2%) were surrendered. Since 2016, the annual number of gibbons received by authorities has steadily increased. Handover motives appear to be overwhelmingly based on legal reasons. Although regarded as ineffective in mitigating trade, law enforcement and fear of the law were the primary reasons for gibbon handovers. Therefore, publicizing successful law enforcement cases of gibbon trade in the media could deter future buyers and reduce demand.